Evaluating vision-related quality of life in preoperative age-related cataract patients and analyzing its influencing factors in China: a cross-sectional study. Issue 1 (December 2015) - Zhu, Min; Yu, Jiaming; Zhang, Jinsong; Yan, Qichang; Liu, Yang
Abstract Background To evaluate vision-related quality of life in preoperative age-related cataract patients in China, using the Chinese version of the National Eye Institute Visual Function Questionnaire-25 (CHI-NEI-VFQ-25), together with analyses of its influencing factors. Methods Cataract patients were interviewed using the CHI-NEI-VFQ-25, and their demographic information was recorded. The Cronbach α coefficient was used to determine the internal consistency of the CHI-NEI-VFQ-25. Multi-trait analyses were used to assess construct validity, including item convergent validity and item discriminant validity. The data were evaluated by descriptive statistical analyses, by the Kruskal–Wallis rank sum test, and by multinomial logistic regression. Results The Cronbach α coefficients were all above 0.8, except for the driving subscale. All items passed the convergent and discriminant validity tests. The composite score was 63.0. The lowest five subscale scores were in general vision (40.0), mental health (37.5), role difficulty (37.5), near vision activities (50.0), and dependence (58.3). Except for the subscale scores of general health and ocular pain, the composite scores and subscale scores were positively associated with the best-corrected visual acuity (BCVA) in the better eye. Multinomial logistic regression showed that sex, age, and educational attainment were significantly associated with the composite score and subscale scores. Conclusions BCVA in the better eye was the most important determinant associated with the decrease in vision-related quality of life. Visual impairment had more impact on the psychosocial parameter than on the other parameters of the patients' quality of life. Among all the demographic characteristics, including sex, age, and educational attainment, influenced the quality of life in age-related cataract patients.